Recent Advances in Osteoclast Biological Behavior - Sun, Yang; Li, Jiangbi; Xie, Xiaoping; Gu, Feng; Sui, Zhenjiang; Zhang, Ke; Yu, Tiecheng (Frontiers in Cell and Developmental Biology, 2021)
With the progress of the aging population, bone-related diseases such as osteoporosis and osteoarthritis have become urgent problems. Recent studies have demonstrated the importance of osteoclasts in bone homeostasis, implying these will be an important mediator in the treatment of bone-related diseases. Up to now, several reviews have been performed on part of osteoclast biological behaviors such as differentiation, function, or apoptosis. However, few reviews have shown the complete osteoclast biology and research advances in recent years. Therefore, in this review, we focus on the origin, differentiation, apoptosis, behavior changes and coupling signals with osteoblasts, providing a simple but comprehensive overview of osteoclasts for subsequent studies.